STEM education in childhood: perceptions of teachers - Fuertes Camacho, M. Teresa; Fernández Morilla, Mónica (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The skills promoted by STEM education are part of basic literac,y and some countries are beginning to recognise their importance in the educational policies of the stage of children from 3 to 6 years old, to develop critical thinking and scientific skills. In this exploratory research, early childhood education teachers were asked about issues related to the meaning, skills, types of activities, needs, obstacles and challenges to integrate it in early childhood education classrooms, as well as about the possibilities of cooking workshops as a laboratory for STEM education.